Overall water effectiveness: a new lean indicator for digital evaluation of water efficiency in industrial processes - Braglia, Marcello; Afy-Shararah, Mohamed; Di Paco, Francesco; Gabbrielli, Roberto; Marrazzini, Leonardo (Elsevier, 2026)
Water management is becoming an increasingly critical challenge for manufacturing industries due to growing environmental concerns, stricter regulatory requirements, and rising pressure from clients demanding more sustainable practices. Efficient and transparent use of water resources is no longer optional but a strategic necessity across industrial sectors. In this paper a new Lean performance indicator for evaluating water usage in industrial processes is presented. The proposed indicator, named Overall Water Effectiveness, aims to systematically assess industrial water performance by quantifying the gap between actual and ideal performance. It builds on the logic of Overall Equipment Effectiveness to identify water-related losses and support informed decision-making for continuous improvement while introducing a comprehensive industrial loss structure specifically designed for water use and consumption. Jointly, two key additional indicators are introduced: one measures how effectively the production process consumes input water, while the other evaluates the dependency on external water sources, taking into account the contributions of recycled and returned water. By translating high-level sustainability goals into actionable operational metrics, this new set of indicators enables the integration of water management into daily industrial operations through a practical, easy-to-use tool. The approach is applied in a major textile manufacturing company, demonstrating its practical utility in evaluating water use and consumption, identifying loss patterns, and leading the identification of improvement actions.
Keywords: Lean manufacturing; Water management; Sustainable management; Overall equipment effectiveness; Textile industry; Digital transformation; 40 Engineering; 4014 Manufacturing engineering; 4609 Information systems